Inside the belly of a beast: individualizing nutrition for young, professional male rugby league players: a review - Kelly, V. G.; Oliver, L. S.; Bowtell, J.; Jenkins, D. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Professional rugby league (RL) football is a contact sport involving repeated collisions and high-intensity efforts; both training and competition involve high energy expenditure. The present review summarizes and critiques the available literature relating the physiological demands of RL to nutritional requirements and considers potential ergogenic supplements that could improve players` physical capacity, health, and recovery during the preparatory and competition phases of a season. Although there may not be enough data to provide RL-specific recommendations, the available data suggest that players may require approximately 6-8 g/kg/day carbohydrate, 1.6-2.6 gg/kg/day protein, and 0.7-2.2 g/kg/day fat, provided that the latter also falls within 20-35% of total energy intake. Competition nutrition should maximize glycogen availability by consuming 1-4 g/kg carbohydrate (~80-320 g) plus 0.25 g/kg (~20-30 g) protein, 1-4 hr preexercise for 80-120 kg players. Carbohydrate intakes of approximately 80-180 g (1.0-1.5 g/kg) plus 20-67 g protein (0.25-0.55 g/kg) 0-2 hr postexercise will optimize glycogen resynthesis and muscle protein synthesis. Supplements that potentially improve performance, recovery, and adaptation include low to moderate dosages of caffeine (3-6 mg/kg) and ~300 mg polyphenols consumed ~1 hr preexercise, creatine monohydrate "loading" (0.3 g/kg/day) and/or maintenance (3-5 g/day), and beta-alanine (65-80 mg/kg/day). Future research should quantify energy expenditures in young, professional male RL players before constructing recommendations.